PENGARUH KOMPOS TERHADAP SIFAT FISIK TANAH DAN PERTUMBUHAN TANAMAN JAGUNG DI INCEPTISOL - Koko Heru Widodo; Zaenal Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The purpose of this study was to elucidate the effect of composting on changes in soil physical properties and to examine the relationship of soil physics properties with plant growth. The method used is a completely randomized block design implemented on the moor land located in the Village Lojejer Wuluhan District, East Java Jember. The study was conducted on 750 m2 of land with an altitude of 14 above sea level. Type of soil that is found in the research field is an Inceptisol having organic material content of 1.1%. Parameters measured aggregate stability, soil pore, bulk density, organic hatter, plant height, leaf number, wet weight of plant, and dry weight of plant. The results showed that addition of several doses of compost improved physical properties of the soil studied. The addition of compost increased the amount of microbes in the soil that played as soil adhesive agents that make the stabile soil aggregate. The soil aggregates stability could increase pores and decrease the weight of the soil content. Composting did not affect the growth of plants because at the time of vegetative growth compost did significantly effect soil physical characteristics.